Indigenisation policy as a vehicle for socio-economic rural development: a case of Chivi community share ownership trust from 2007-2014. - Mavunganidze, Nedfant (Midlands State University, 2017)
The onset of the colonial rule in Zimbabwe during the 1890s retarded the socio-economic fortunes of the country and ultimately led to the impoverishment of the blacks. Rural communities in Zimbabwe have suffered centuries of poverty and underdevelopment since colonialism segregated them from development and took them as reservoirs of cheap labor for the advancement of settler colonial economy. The Indigenisation programme is one among other empowerment programmes designed to redress the historical injustices and inequalities imposed on rural communities by the colonial governments. This research examines the impact of the Indigenisation and Economic Empowerment programme as a vehicle to promote socio-economic rural development in Zimbabwe and Chivi district in particular. Data were collected from both primary and secondary sources such as policy statements, journals, books, articles and internet sources on rural empowerment and Indigenisation. Interviews were drawn from government officials, community leaders such as Chiefs, village heads and councilors, teachers and the generality of the population in Chivi district. The investigation established that the Indigenisation programme delivered what I wish to call patchy development because the projects of the programme have promoted development only in a few selected areas of the district. The programme has the potential to unlock the development puzzle in Zimbabwe but various factors such as lack of capital, political influence of some powerful individuals who interfered with programme implementation, and corrupt tendencies by agents for proposed change among others have hindered the outcome of tangible results in Chivi district and Zimbabwe in general